1973
DOI: 10.1063/1.1680033
|View full text |Cite
|
Sign up to set email alerts
|

Generalized molecular distribution functions

Abstract: Molecular distribution functions are concerned with the probability densities of observing a set of n particles at some specified locations. The generalized molecular distribution functions ``load'' the n particles with additional information, which may include or exclude their locations. It is argued that the study of these functions may provide a new insight into the local properties of the molecules in the liquid state. A sample of computed generalized molecular distribution functions by the Monte Carlo tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1975
1975
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…He investigated the structure of the pure fluid , and a dilute hydrophobic solution , using an integral equation formalism. Then, he explored several parameter sets using NVT Monte Carlo simulations at a single phase point for each parametrization, and obtained more accurate distributions of the pure fluid , Consequently, the Ben-Naim model was all but neglected until recently when Andaloro and Sperandeo-Mineo showed that it was simple enough to teach students about hydrophobicity without high-powered computers …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…He investigated the structure of the pure fluid , and a dilute hydrophobic solution , using an integral equation formalism. Then, he explored several parameter sets using NVT Monte Carlo simulations at a single phase point for each parametrization, and obtained more accurate distributions of the pure fluid , Consequently, the Ben-Naim model was all but neglected until recently when Andaloro and Sperandeo-Mineo showed that it was simple enough to teach students about hydrophobicity without high-powered computers …”
Section: Introductionmentioning
confidence: 99%
“…Then, he explored several parameter sets using NVT Monte Carlo simulations at a single phase point for each parametrization, and obtained more accurate distributions of the pure fluid. 30 Concurrently, more realistic 3D models were being developed. 17,18 Consequently, the Ben-Naim model was all but neglected until recently when Andaloro and Sperandeo-Mineo showed that it was simple enough to teach students about hydrophobicity without high-powered computers.…”
Section: Introductionmentioning
confidence: 99%
“…In the present article, we describe a molecular dynamics simulation of a two-dimensional system with a Lennard-Jones interaction potential. The essential features of Lennard-Jones models are common in two and three dimensions (Ben-Naim 1973, Toxvaerd 1975. Therefore two-dimensional simulations can qualitatively account for the behaviour of real fluids.…”
Section: Introduction Great Progress Hasmentioning
confidence: 99%